Integrasi Nilai-Nilai Islam dalam Pengelolaan Sumber Daya Manusia di Lembaga Pendidikan - Ayunda Salsabila; Zulfani Sesmiarni (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The success of educational institutions in achieving their goals and visions depends on effective human resource (HR) management. In this article, we focus on principles such as honesty (ṣidq), justice (’adl), responsibility (amanah), and cooperation (ta’āwun), which are integrated into human resource management practices in educational institutions. This method not only improves work ethic and professionalism, but also strengthens the spiritual character of educators and education personnel. This study shows with descriptive qualitative methods that applying Islamic principles in the recruitment, training, performance evaluation and career development processes can produce a harmonious and meaningful work environment. In addition, it is evident that this integration increases employee loyalty, motivation and job satisfaction. These results have significant consequences for the development of value-based human resource management, especially in Islamic educational institutions.